Potential of desiccation-tolerant plant growth-promoting rhizobacteria in growth augmentation of wheat (Triticum aestivum L.) under drought stress - Ajay Shankar; Vishal Prasad (Frontiers in Microbiology, 2023)
Wheat (Triticum aestivum L.) yield and physiology are adversely affected due to limited water availability. However, desiccation-tolerant plant growth-promoting rhizobacteria (DT-PGPR) are potential candidates that can overcome the negative impacts of water stress. In the present study, a total of 164 rhizobacterial isolates were screened for desiccation tolerance up to −0.73 MPa osmotic pressure, of which five isolates exhibited growth and expression of plant growth properties under the influence of desiccation stress of −0.73 MPa. These five isolates were identified as Enterobacter cloacae BHUAS1, Bacillus cereus BHUAS2, Bacillus megaterium BHUIESDAS3, Bacillus megaterium BHUIESDAS4, and Bacillus megaterium BHUIESDAS5. All five isolates exhibited plant growth-promoting properties and production of exopolysaccharide (EPS) under the impact of desiccation stress. Furthermore, a pot experiment on wheat (variety HUW-234) inoculated with the isolates Enterobacter cloacae BHUAS1, Bacillus cereus BHUAS2, and Bacillus megaterium BHUIESDAS3 exhibited a positive influence on the growth of wheat under the condition of water stress. A significant improvement in plant height, root length, biomass, chlorophyll and carotenoid content, membrane stability index (MSI), leaf relative water content (RWC), total soluble sugar, total phenol, proline, and total soluble protein, were recorded under limited water-induced drought stress in treated plants as compared with non-treated plants. Moreover, plants treated with Enterobacter cloacae BHUAS1, Bacillus cereus BHUAS2, and Bacillus megaterium BHUIESDAS3 depicted improvement in enzymatic activities of several antioxidant enzymes such as guaiacol peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX). Beside this significant decrease in electrolyte leakage, H2O2 and malondialdehyde (MDA) contents were also recorded in treated plants. From the results obtained, it is evident that E. cloacae BHUAS1, B. megaterium BHUIESDAS3, and B. cereus BHUAS2 are the potential DT-PGPR having the capability to sustain growth and yield, alleviating the deleterious effect of water stress in wheat.